DAMPAK BULLYING VERBAL PADA KESEJAHTERAAN PSIKOLOGIS REMAJA: SYSTEMATIC LITERATURE REVIEW - Ikhwan, Mursyidul; Firman, Firman; Netrawati, Netrawati; Gustri Handayani, Puji (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2025)
Verbal bullying is one of the most common forms of violence experienced by adolescents and has a serious impact on their psychological well-being. This study aims to comprehensively examine the impact of verbal bullying on adolescents' psychological well-being through a systematic literature review. Data was collected from 10 international scientific articles published between 2020 and 2025, using keywords such as “Verbal Bullying, Verbal violence, Verbal abuse, Taunting, Name-calling”. The results of the 10 reviewed articles indicate that verbal bullying can lead to various psychological disorders, such as depression, anxiety, decreased self-confidence, trauma, and impaired social relationships. These impacts tend to be more severe for adolescents with specific psychological vulnerabilities or who experience verbal bullying. These findings highlight the need for school- and family-based preventive interventions that are sensitive to psychological, social, and gender factors. Further research is recommended to develop evidence-based intervention programs to strengthen adolescents' psychological resilience and reduce the prevalence of verbal bullying in educational settings.